Silicon Nanodevices - Radamson, Henry; Wang, Guilei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of scientific articles which brings research in Si nanodevices, device processing, and materials. The content is oriented to optoelectronics with a core in electronics and photonics. The issue of current technology developments in the nanodevices towards 3D integration and an emerging of the electronics and photonics as an ultimate goal in nanotechnology in the future is presented. The book contains a few review articles to update the knowledge in Si-based devices and followed by processing of advanced nano-scale transistors. Furthermore, material growth and manufacturing of several types of devices are presented. The subjects are carefully chosen to critically cover the scientific issues for scientists and doctoral students.